Internal Migration In India: Evidence From Census Data, 1991-2011 - Dr. Kalosona Paul , Abinash Bauri , Jibanbandhu Gayak , Khalid Raja Khan , Sathi Mandal , Arup Sen , Uttam Kumar Patra (Migration Letters, 2022)
Internal migration is a key factor influencing a country’s population size, structure, characteristics as well as socio-economic development. Over the years, with increased socio-economic development, internal migration has increased in the country. The Census of India reveals that in 2011, migrants based on place of last residence were 453 million, accounting for 37.5 per cent of the total population in India, which is twice the number in the year 1971 (159 million). The key objective of this paper is to explain the flow of interstate migration in terms of trends, patterns, streams and reasons for in & out-migration, 2011. Secondary data from the Census of India, from 1991-2011 has been used to calculate the male, female and total migration rate, stream-wise distribution, and reasons for migration (1991-2011). The study finds that both the male and female migration rates increased (male 14.79 to 23.03 & female 41.64 to 52.17) from 1991 to 2011, with rural-to-rural migration being more dominant than other streams (U-R and U-U )for both the sexes in India. Marriage is the main reason for total migration but males were more prone to out-migrate for job/employment. The stream of rural to urban migration showed a higher percentage (48.5%) in 2011 due to increased employment opportunities in urban areas. In terms of interstate migration, Goa recorded a higher percentage than other states, throughout the time. However, the rate of interstate out-migration was more significant for Bihar (30 per 1000 population) attributed to employment opportunities. Union Territory (UT) like Chandigarh (121.3 per 1000 population) contained huge migrants to about every reason for migration in India, 2011. During the period, intra-district migration steadily declined with education and employment being the major reasons for the migration of women in recent times, then marriage.